Children’s perspectives of their everyday food practices: insights to inform policy and interventions - Sophie Wright-Pedersen; Helen Vidgen; Danielle Gallegos (PLoS ONE, 2026)
Children’s everyday food practices have a profound impact on their physical, mental, cultural and social health and wellbeing. Grounded in social practice theory, the focus of this paper is the examination of the performance of food practices, rather than the practitioner. This approach supports health promoting efforts to move away from victim blaming and instead explore the intersections between individual, social and structural determinants of food practices. With foundations in the New Sociology of Childhood, this article explores eight- to twelve-year-old children’s perspectives of the enablers and constraints to their performances of everyday food practices through a social practice theory lens. Children participated in sequential creative draw-and-tell interviews and Photovoice methods. Through abductive analysis of qualitative data, diverse interlinking configurations of the meanings, materials and competences were attributed by children as either facilitating or constraining food practice performances further impacted by transitioning times, places, social settings and contexts. A case study of food shopping practices was able to present a holistic narrative of how individual, social and structural determinants intertwined across the temporal and spatial dimensions. This study showcases how a social practice led approach that privileges children’s voices can be used to inform more holistic, equitable, engaging and effective health policy and practice that endeavour to impact children’s routine and habitual food practices.